Clinical study of central serous chorioretinopathy presenting in a tertiary care centre - Dalai, Ramamani; Rout, Rajashree; Pradhan, Manjula; Nanda, Prasanta Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Central Serous chorioretinopathy (CSCR) is one of the common causes of visual handicap affecting young people of highly intellectual professionals at the peak of their career which can lead to irrecoverable loss of vision. Methods: The present prospective observational population-based study was conducted in the Department of Ophthalmology, S.C.B. Medical College, Cuttack, Odisha from October 2013 to September 2015. The total number of patients attended the Outpatient Department (OPD) during the study period were 1,83,199. Amongst which 123 patients diagnosed to have CSCR were selected for the present study. Results: Incidence of CSCR during in this study period was 0.06%. The age group most commonly affected was 31 to 40 years. Males were affected 7 times more commonly than females. Increased incidence was noticed in bank employees (21.1 %) and IT professionals (17.8%). Conclusions: There was increased incidence of the disease in people under stressful life condition.